Karakteristik Thermal Shortening Minyak Biji Karet, Minyak Ikan, dan Stearin Sawit Menggunakan Differential Scanning Calorimetry (DSC) - Sumartini Sumartini; Nirmala Efri Hasibuan; Sellen Gurusmatika (Jurnal Agritechno, 2021)
The purpose of this research is often faced in making spreads products such as shortening is the difficulty of producing products with the expected melting point. Chemical interesterification is considered cheaper, simpler, easier to control, the temperature used is not too high, thereby reducing the possibility of trans fatty acids forming. The purpose of this study was to determine the characteristics of the thermal profile and melting point of shortening through two different lipid modifications, blending (NIE) and chemical interesterification (CIE). The research method used was a completely randomized design (CRD) with 10 treatment ratios to determine the melting characteristics of shortening using DSC (Differential Scanning Calorimetry). The results showed that the melting point value was in the melting temperature range (40-49 ° C). Based on the Thermal Characteristics the ratio 90/5/5 (CIE 4) and 80/10/10 (CIE 3) have 3 and 4 low melting point peaks. Based on these data it can be concluded that the melting point and thermal profile of chemical interesterification are lower than blending, this proves that chemical intereterification is able to create new shortening fats with certain plasticity and provide melting characteristics according to commercial shortening.